Interleukin-35 pathobiology in periodontal disease: a systematic scoping review - Patrick R. Schmidlin; Mandana Dehghannejad; Omid Fakheran (BMC, 2021)
Abstract Background Interleukin (IL)-35 is a novel anti-inflammatory cytokine that is produced by regulatory T cells. IL-35 mediates immunological functions and plays a protective role in several diseases such as asthma and rheumatoid arthritis. However, the role of IL-35 in gingivitis and periodontitis remains unclear. The aim of this study was to systematically review the literature and collecting the available evidence regarding the role of IL-35 in pathogenesis of periodontal disease. Methods A systematic search of electronic databases including MEDLINE, Google Scholar, Cochrane Library, Web of Science, and Scopus was conducted in November 2020 to identify studies addressing the Interleukin-35 pathobiology in periodontal disease. The identified studies were subjected to pre-identified inclusion criteria. The retrived papers were assessed by the authours independently and consensus was reached in cases where disagreement occurred. Articles written in languages other than English, case reports, letters to editors, conference abstracts, theses, and dissertations were excluded from the review. Results A total of 176 possibly relevant articles were identified through the search strategy. Finally, 15 papers which met the criteria of eligibility were included in this review by consensus. The included articles were classified based on their design and level of evidence.Three subclinical study, ten cross sectional investigation and two randomized clinical trials constituted the final set of studies in this review. At preclinical level, Il-35 showed inhibitory characteristics regarding alveolar bone resorption of animal periodontitis models. The results of observatory human studies confirmed the presence of high levels of IL-35 in saliva, GCF, serum, and gingival biopsies of patients suffering from inflammatory periodontal disease. Moreover, two included clinical trials showed that non-surgical periodontal therapy could downregulate IL-35 production in chronic periodontitis patients. Conclusion Interleukin-35 has an undeniable role in pathobiology of inflammatory periodontal disease. Further well-controlled studies are needed to better elucidate the functional pattern of IL-35 in pathogeneisis of gingival and periodontal disease.